A microfluidic immunosensor for automatic detection of carcinoembryonic antigen based on immunomagnetic separation and droplet arrays. Issue 9 (14th March 2023) - Hu, Haoran; Cai, Gaozhe; Gao, Zehang; Liang, Cheng; Yang, Fengna; Dou, Xiaohui; Jia, Chunping; Zhao, Jianlong; Feng, Shilun; Li, Bei
Abstract : Using immunomagnetic separation technology to enrich the target in the sample, combined with solid-phase surface modification technology to complete the quantitative detection of the sample concentration, enabling a more simplified detection process. Abstract : Diagnosis of cancer by biomarkers plays an important role in human health and life. However, current laboratory techniques for detecting cancer biomarkers still require laborious and time-consuming operation by skilled operators and associated laboratory instruments. This work presents a colorimetric biosensor for the rapid and sensitive detection of carcinoembryonic antigen (CEA) based on an automated immunomagnetic separation platform and a droplet array microfluidic chip with the aid of an image analysis system. Immunomagnetic nanoparticles (MNPs) were used to capture CEA in the samples. CEA-detecting antibodies and horseradish peroxidase (HRP) were modified on polystyrene microspheres (PS), catalysing hydrogen peroxide and 3, 3′, 5, 5′-tetramethylbenzidine (TMB) as signal outputs. Color reaction data were analyzed to establish a CEA concentration standard curve. The movement of MNPs between droplets in the microfluidic chip is achieved using an automatically programmable magnetic control system. This colorimetric biosensor has been used for the simultaneous detection of six CEA samples ranging from 100 pg mL −1 to 100 ng mL −1 with a detection limit of 14.347 pg mL −1 in 10 min, following the linear equation: y = −4.773 ln( x ) + 156.26 with a correlation of R 2 = 0.9924, and the entire workflow can be completed within 80 minutes. The microfluidic immunosensor designed in this paper has the advantages of low cost, automation, low sample consumption, high throughput, and promising applications in biochemistry.